Komunikasi Interpersonal Himpunan Mahasiswa Islam (HMI) dalam Membentuk Soft Skill Mahasiswa Ilmu Komunikasi Universitas Islam Negeri Sumatera Utara Medan - Nazira, Syafiq; Kholil, Syukur; Rasyid, Abdul; Hutagalung, Syahrial Arif (Medan Resource Center, 2025)
This study explores the role of interpersonal communication among senior members, administrators, and general members of the Islamic Student Association (HMI) at the Faculty of Social Sciences (FIS), State Islamic University of North Sumatra (UIN Sumatera Utara), in fostering soft skills among Communication Science students. Employing a qualitative research design with a phenomenological approach, the study investigates lived experiences and observable phenomena through methods of observation, interviews, and documentation. Data were analyzed through a process of reduction, presentation, and conclusion drawing conducted concurrently with data collection. Findings indicate that interpersonal communication within the HMI FIS UIN Sumatera Utara Commission is both effective and progressive in developing soft skills. Evidence includes high participation rates among Communication Science students, consistently strong soft skill performance across members, and the successful implementation of work programs. The effective interpersonal dynamics between senior members and administrators positively influence the development of essential soft skills among members, such as collaboration, communication, creativity, honesty, responsibility, leadership, time management, problem-solving, interpersonal relations, affective and cognitive abilities, and psychomotor skills.